Influence of biochar and EDTA on enhanced phytoremediation of lead contaminated soil by Brassica juncea. (May 2021) - Rathika, R.; Srinivasan, P.; Alkahtani, Jawaher; Al-Humaid, L.A.; Alwahibi, Mona S.; Mythili, R.; Selvankumar, T.
Abstract: Phytoremediation technology is an eco-friendly technology for the treatment of the polluted environment. Conversely, the natural and synthetic amendments have been revealed to improve the heavy metal phytoextraction from polluted soils with hyperaccumulation and/or non-hyper accumulating plants. This study evaluated the synergistic effect of biochar (BC) and EDTA to enhance phytoextraction of heavy metal lead (Pb) from artificially polluted soil by Brassica juncea . The BC and EDTA amendment enhanced the growth and survival of B. juncea under Pb stress environment. BC and EDTA significantly increased the biomass of B. juncea and significantly increased the total chlorophyll content in the combined amendment of BC and EDTA (22.2 mg/g) compared to the individual amendment of BC (12.8 mg/g) and EDTA (12.2 mg/g) respectively. The combined use of EDTA and biochar showed enhanced Pb uptake (60.2 mg/g) compared to control (10.0 mg/g). The order of Pb uptake was found to be BC + EDTA (60.2 mg/g) ˃ EDTA (23.5 mg/g) ˃ BC (22. 0 mg/g) ˃ control (10.0 mg/g). The maximum activity of SOD (35.2 ± 1.2 U/mg), POD (47.0 ± 1.8 U/mg) and CAT (28.0 ± 1.0 U/mg) was obtained in the mixed application of EDTA and BC. The obtained results revealed that the combined use of BC and EDTA was the most advantageous option for the treatment of Pb contaminated soil as compared to individual amendments. Highlights: Synergistic effect of biochar (BC) and EDTA to enhance phytoextraction of lead (Pb) contaminated soil investigated. Combined use of EDTA and biochar showed enhanced Pb uptake (60.2 mg/g). Pb uptake was found to be BC+EDTA (60.2 mg/g) ˃ EDTA (23.5 mg/g) ˃ BC (22. 0 mg/g) ˃ control (10.0 mg/g).